STUDENTS' EXPERIENCES OF 2D AND 360° VIDEOS WITH OR WITHOUT A LOW-COST VR HEADSET: AN EXPERIMENTAL STUDY IN HIGHER EDUCATION - Alamäki, Ari; Dirin, Amir; Suomala, Jyrki; Rhee, Cheul (Journal of Information Technology Education: Research, 2021)
Aim/Purpose This case study examines students' affective responses to and relationships with two-dimensional (2D) and 360° videos that were experienced with or without low-cost virtual reality (VR) headsets. Background The prior research on low-cost VR technology is scant. Schools and universities are not financially able to purchase tens or hundreds of expensive inbuilt VR headsets. Therefore, we recommend an alternative, low-cost solution. Methodology We conducted the experiment with students' (N=100) responses to videos and VR technologies used in a higher education setting. We also applied a quantitative research approach examined in light of media richness and affective experience theories. Contribution This study provides evidence of the integral role that VR technologies and 360° video content play, because using low-cost VR headsets potentially decreases the initial affective experiences of 360° videos among students. Although VR headsets improve media richness, they might simultaneously weaken students' overall affective experiences if they experience usability challenges. Findings The results showed that using low-cost VR headsets decreased positive user ex periences when they were watching 360° videos. The 360° video experience was noted to be better without low-cost VR headsets. Low-cost VR headsets with a smartphone and 360° videos were found to be complicated to set up and use among first-time users. However, 360° videos created a more positive affect than did 2D videos. We also found that the positive affect of videos enhanced the social sharing intention. Recommendations Educational institutes and teachers with limited financial budgets need to plan for Practitioners and manage courses that increases their need to adopt low-cost VR headsets. However, a poor initial user experience of low-cost VR technology usability might create negative student attitudes, which might hinder VR's adoption rate in higher education. Recommendations This study provides a new understanding about students' affective experiences for Researchers of 2D videos and 360° videos with and without low-cost VR headsets. The results show that positive user experiences of 2D and 360° videos enhance students' interest in sharing and collaboration in digital learning environments. Impact on Society The results help educators to predict possible usability challenges in selecting the proper rich media for different learning situations. Additionally, the results assist educators to design VR assisted courses that motivate students. Future Research The experimental comparison of different VR solutions and traditional learning technologies merits further examination. Additionally, more research is needed to determine the relationship of VR technologies, video content and learning methods, because technological features and content are tightly integrated in VR.
Keywords: 360° video; affective user experience; higher education; VR technologies